TDZ pulsing evaluation on the in vitro morphogenesis of peach palm - Graner, Érika Mendes; Oberschelp, Gustavo Pedro Javier; Brondani, Gilvano Ebling; Batagin-Piotto, Katherine Derlene; Almeida, Cristina Vieira de; Almeida, Marcílio de (2018)
Peach palm (Bactris gasipaes Kunth.) cropping is an excellent alternative to native species exploitation; nevertheless, the problems with seed germination and conventional propagation justify the use of in vitro culturing. Aiming to asses TDZ pulsing effect on B. gasipaes morphogenesis, explants obtained from unarmed microplants were maintained in two treatments, half of them in MS free medium (without growth regulator) and the other half in MS with TDZ (0.36 μM). Both groups were transferred to growth regulator-free MS medium following 14 days of culture. After 84 days of culture, TDZ pulsing increased the growth and development of the shoots, restricted the growth and development of the roots, with no influence on adventitious bud induction or somatic embryogenesis. Furthermore, development of prickles, thickening of roots and chlorotic leaves were noted under TDZ pulsing. Leaf sheath histological analysis showed an epidermal origin and no vascularization of these prickles.